Evaluating the implementation of community engagement guidelines (EVALUA GPS project): a study protocol - Vicente Gea-Caballero; Carmen Belén Benedé Azagra; Ana Maria García; Viola Cassetti; María Victoria López-Ruiz; Marta Domínguez; Alba Gallego-Royo; Catalina Nuñez; Joan Josep Paredes-Carbonell; Luis Angel Pérula-De Torres; Marina Pola-Garcia; Aldecoa Landesa Susana; et al. (BMJ Open)
Introduction The EVALUA GPS project aims to evaluate the impact of the implementation of the National Institute for Health Care and Excellence (NICE) guideline ‘Community engagement: improving health and well-being and reducing health inequalities’ adapted to the Spanish context.Methods and analysis Phase I: A tool will be designed to evaluate the impact of implementing the recommendations of the adapted NICE guideline. The tool will be developed through a review of the literature on implementation of public health guidelines between 2000 and 2021 and an expert’s panel consensus. Phase II: The developed tool will be implemented in 16 community-based programmes, acting as intervention sites, and 4 controls through a quasi-experimental pre–post study. Phase III: A final online web tool, based on all previously collected information, will be developed to support the implementation of the adapted NICE guidelines recommendations in other contexts and programmes.Data collection and analysis Data will be collected through surveys and semistructured interviews. Quantitative and qualitative data will be analysed to identify implementation scenarios, changes in community engagement approaches, and barriers and facilitators to the implementation of the recommendations. All this information will be further synthesised to develop the online tool.Ethics and dissemination The proposed research has been approved by the Clinical Research Ethics Committee of Aragon. Results will be presented at national and international conferences and published in peer-reviewed open access journals. The interactive online tool (phase III) will include examples of its application from the fieldwork.